Characterizing and predicting 21700 NMC lithium-ion battery thermal runaway induced by nail penetration. (5th June 2022) - Shelke, Ashish V.; Buston, Jonathan E.H.; Gill, Jason; Howard, Daniel; Abbott, Katie C.; Goddard, Steven L.; Read, Elliott; Howard, Gemma E.; Abaza, Ahmed; Cooper, Brian; Wen, Jennifer X.
Highlights: Pioneering CFD predictions of nail penetration induced TR in 21700 cylindrical cells. Internal heat generation is coupled with external convective and radiative heat exchange. New tests to establish the differences in radial and axial penetration of cylindrical cells. Fill experimental gaps by quantify the effects of contact resistance and external heat transfer. The generic nature of the CFD based predictive tool can be easily adapted for other cell types. Abstract: Combined numerical and experimental studies are conducted to characterise 21, 700 cylindrical lithium-ion battery (LIB) thermal runaway (TR) induced by nail penetration. Both radial and axial penetrations are considered for 4.8 Ah 21, 700 NMC cell under 100% state of charge. Heat generation from the decomposition of the cell component materials are analysed. The maximum cell surface temperature rise and time to reach it in both types of penetration tests are compared. Snapshots from the video footages captured by three high definition and one high speed cameras shade light on the dynamic processes of spark ejection and flame evolution. A generic predictive tool is developed within the frame of the in-house version of open-source computational fluid dynamics code OpenFOAM for nail induced TR. The code treats the cell as a lumped block with anisotropic thermal conductivities and considers heat generation due to nail induced internal short circuit resistance, exothermic decomposition reactions and heat dissipation through convective and radiative heat transfer. Validation with the current measurements shows promising agreement. The predictions also provide insight on the magnitudes of heat generation due to internal short circuit resistance, decompositions of solid electrolyte interphase layer (SEI), anode, cathode and electrolyte. Parametric studies further quantify the effects of cell internal short circuit resistance, contact resistance between the nail and cell, convective heat transfer coefficient and cell surface emissivity on TR evolution.